Wireless Sensor Device For Health Monitoring, Using ZigBee Technology - Mohamad Zulhilmi Bin Zaini, Mohamad Zulhilmi (Universiti Teknologi Petronas, 2011)
In this project, we develop a portable real-time wireless health monitoring system. Goal of the project is to monitor patient’s heart rate. The system was designed and implemented using ZigBee wireless technologies. All data will be transferred within a group of wireless network to database computer system. The sensor modules were designed for low power operation so that it can last long. This project is divided into two phase which is sensor design phase and transmission phase. In the first phase, sensor unit consists of two types of LEDs and photodiode that is facing to a patient’s fingertip and microcontroller unit for interacting with ZigBee module. Second phase involve ZigBee module to communicate with heart rate sensor. ZigBee module gets all commands from microcontroller unit and it works on both transmitting and receiving process. Throughput from ZigBee receiver will be displayed at computer for monitoring purpose. This method can be developed into a noninvasive technique to measure body temperature and blood pressure.